Pentingnya Meningkatkan Literasi dan Minat Belajar Siswa-siswi SMPN 1 Huamual Belakang dan SDN Allang Asaude - Jolanda Tomasouw; Brian Saputra Manurung; Ronald Darlly Hukubun; Wiwien G. Hukubun; Feronika Pulamajen (Yayasan Literasi Sains Indonesia, 2025)
Improving literacy and interest in learning at SMPN 1 Huamual Belakang and SDN Allang Asaude is essential to prepare students for future educational and life challenges. Literacy, including the ability to read, write and think critically, is a key foundation in an effective learning process. Socialization of the importance of improving literacy and interest in learning is the first step in overcoming low literacy and interest in learning that occurs at SMPN 1 Huamual Belakang and SDN Allang Asaude. This socialization aims to provide awareness and insight to students about the importance of literacy skills and provide tips or ways to increase interest in learning. This socialization activity used the lecture method which was attended by students, teachers and school principals. The results of the socialization activities showed a change in mindset about the importance of literacy skills and finding effective ways to increase interest in learning. Improving literacy and interest in learning should be a top priority through innovative and collaborative programs. Therefore, this socialization is expected to build students' awareness of literacy and find the right way to increase interest in learning so that students are not only academically smart but also have a strong character to face the future.